The Effectiveness of the Adiwiyata Program in Strengthening Environmental Culture at MTs PPMI Assalaam: A Study of the CSE-UCLA Evaluation Model - Triyatno; Ahmad Muhibbin; Sigit Haryanto (South Sulawesi Education Development (SSED), 2025)
This study aims to evaluate the effectiveness of the Adiwiyata Program in strengthening environmental culture at MTs PPMI Assalaam using the CSE–UCLA evaluation model. A qualitative research method with a descriptive-analytical approach was applied through interviews with the madrasah principal, Adiwiyata coordinator, teachers, students, and employees, as well as program observation and documentation. The results show that the Adiwiyata program has been implemented systematically, starting from system assessment, planning, implementation, improvement, and certification. The integration of Islamic values ​​and Islamic boarding school culture is an important factor in shaping environmentally conscious character. This program has succeeded in creating a sustainable, participatory, and innovative school culture, as well as improving the institution's reputation through Adiwiyata certification. Recommendations are provided for strengthening curriculum integration, digital innovation, and post-certification program sustainability. Keywords: adiwiyata, environmental culture, CSE–UCLA, islamic education, program evaluation